2009
DOI: 10.1007/s12034-009-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Materials science research for sodium cooled fast reactors

Abstract: The paper gives an insight into basic as well as applied research being carried out at the Indira Gandhi Centre for Atomic Research for the development of advanced materials for sodium cooled fast reactors towards extending the life of reactors to nearly 100 years and the burnup of fuel to 2,00,000 MWd/t with an objective of providing fast reactor electricity at an affordable and competitive price.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Void swelling, phase instabilities, irradiation creep occur due to displacement of atoms by fast speeding neutrons. Such challenges are overcome by altering chemical composition/microstructure of stainless steels, for instance, incorporation of minor alloying elements like Ti, Si, and P to reduce the void swelling resistance of austenitic steels as well as altering the thermo-mechanical treatment for instance, refining of prior austenite grain size and tempering to achieve high toughness with optimum strength for ferrite/martensite stainless steels [24]. Recent research on application of stainless steels as nuclear fuel rod cladding and fuel assembly components have showed that yttrium oxide precipitates act as stable obstacles for dislocation movement and help in arresting irradiation creep of both austenitic and ferritic/martensitic stainless steels [25,26].…”
Section: Stainless Steel For Nuclear Applicationsmentioning
confidence: 99%
“…Void swelling, phase instabilities, irradiation creep occur due to displacement of atoms by fast speeding neutrons. Such challenges are overcome by altering chemical composition/microstructure of stainless steels, for instance, incorporation of minor alloying elements like Ti, Si, and P to reduce the void swelling resistance of austenitic steels as well as altering the thermo-mechanical treatment for instance, refining of prior austenite grain size and tempering to achieve high toughness with optimum strength for ferrite/martensite stainless steels [24]. Recent research on application of stainless steels as nuclear fuel rod cladding and fuel assembly components have showed that yttrium oxide precipitates act as stable obstacles for dislocation movement and help in arresting irradiation creep of both austenitic and ferritic/martensitic stainless steels [25,26].…”
Section: Stainless Steel For Nuclear Applicationsmentioning
confidence: 99%
“…In the past several decades, the fuel system of UO2 pellets and Zr alloy cladding applied to light water reactors (LWRs) has been continuously optimized to obtain more reliable and excellent performance. Simultaneously, the research on other types of nuclear fuel cladding and pellets applied to fast breeder reactors and generation-IV reactors has carried out by many countries [1]. The 2011 Fukushima accident has made the safety of nuclear reactors highly valued.…”
Section: Introductionmentioning
confidence: 99%